Exercise and the growth hormone-insulin-like growth factor axis - Frystyk, J. (Medicine & Science in Sports & Exercise, 2010)
Exercise is a robust physiological stimulator of the pituitary secretion of growth hormone (GH), and within approximately 15 min after the onset of exercise, plasma GH starts to increase. GH and its primary downstream mediator, insulin-like growth factor I (IGF-I), play a critical role in formation, maintenance, and regeneration of skeletal muscles. Consequently, it seems logical to link the exercise-induced stimulation of GH with the hypertrophy observed in exercising muscles. GH stimulates circulating (endocrine) as well as locally produced (peripheral) IGF-I, which acts through autocrine/paracrine mechanisms. However, it remains to be clarified whether skeletal muscle hypertrophy after exercise is stimulated primarily by endocrine or paracrine/autocrine IGF-I. Early cross-sectional studies have observed positive correlations between circulating IGF-I levels and GH secretion, respectively, and indices of fitness. However, longitudinal exercise studies have shown that it is possible to increase muscle strength, performance, and VO2max without concomitant and robust changes in circulating IGF-I, indicating that the effect of exercise on skeletal muscles is mediated via paracrine/autocrine IGF-I rather than endocrine IGF-I. So far, most exercise studies have investigated the concentration of immunoreactive IGF-I in serum or plasma, obtained after extraction of the IGF-binding proteins (i.e., total IGF-I). However, several of the newer exercise studies have included measurement of free IGF-I as well as bioactive IGF-I. The aim of this review was to discuss whether measurement of free and/or bioactive IGF-I have increased our knowledge on the processes that link exercise, muscle hypertrophy, and GH/IGF-I axis. Thus, the current review will discuss (i) the different IGF-I assay methodologies and (ii) the current literature on free, bioactive, and immunoreactive (total) IGF-I in exercising subjects.